Avaliação radiográfica da abertura do intervalo glenoumeral na artroscopia do ombro em decúbito dorsal modificado: (Cadeira de Praia) - Mario Roberto Chaves Correa Filho (2018)
Arthroscopy is indispensable in the diagnosis and treatment of several intra-articular and extra-articular lesions of the shoulder and can be performed with the patient positioned in lateral or modified dorsal decubitus (Beach Chair Position), according to the surgeon's preference. The lateral decubitus, by systematically employing static traction of the upper limb, theoretically provides greater opening of the glenohumeral interval (GHI) and is, therefore, considered by many as the ideal technique for the treatment of instability of the shoulder. It appears that there are no in vivo studies comparing the amount of intra-articular visualization obtained in individuals positioned in lateral decubitus position as opposed to those positioned in modified dorsal decubitus position. Nor there are studies measuring the opening range of the GHI obtained with either position. Anatomical differences between individuals, different degrees of relaxation due to anesthesia, and the diversity and magnitude of the lesions in each shoulder are probably the reasons that explain why such studies have not yet been conducted. Because of these said limitations, it was decided to measure the GHI radiographically at 3 points, in different positions of the upper limb in the coronal plane, with the patient anesthetized and positioned in modified dorsal decubitus position immediately before being submitted to shoulder arthroscopy, and posteriorly comparing the results to those obtained in a group of similar individuals, using the same methodology. The angulations of the upper limb in the coronal plane studied were chosen in order to simulate those that are commonly used in the lateral decubitus. The results of this radiographic study indicate that the longitudinal traction of the adducted upper limb was the preponderant factor in obtaining the greater GHI opening range in the upper point; in the middle point, the traction associated to the cushion interposition in the axillary region, or the longitudinal traction of the adducted upper limb, were the predominant factors; in the inferior point, the traction associated to the cushion interposition in the axillary region, was the predominant factor.